Two approaches to effective ventilation system design for the biomedical device and pharmaceutical industries. (8th January 2008) - Handy, Rodney G.; Goodman, Dave; Odukomaiya, Sean; Rodriguez, Monica; Whitfield, Michael; Ahmed, Waqar; Jackson, Mark
This paper provides two alternative solutions to the difficult task of providing adequate ventilation to operations found in the biomedical device and pharmaceutical manufacturing industries. The first approach involves a two-tier strategy that includes an isolation chamber and an appropriately designed local exhaust hood. The second approach involves the design of modular, walk-in hood. Mechanical and electrical design and development criteria for each option are delineated, and advantages and limitations are elucidated for both systems. Future efforts will target the testing of these two approaches under laboratory conditions to assess the merits of each.